JIWA KEPEMIMPINAN KEPALA SEKOLAH PAUD TERHADAP PERAN PENTING KINERJA GURU - Anna Prassasty (QURROTI, 2025)
This study was conducted to determine how much the principal's leadership spirit affects the performance of Early Childhood Teachers in the teaching and learning process to achieve the desired learning objectives. In early childhood education, the teacher's task is heavier by having to provide learning for children who are still very young, the burden of providing a foundation of knowledge for children's provisions for further education. The type of research approach carried out by examining theories, concepts, and related principles. The results of this study are that a leader who can be the vanguard of problems experienced every day is a principal who can be a motivator, facilitator, and supervisor, to help provide support to teachers, not burdening teachers who are not in accordance with their duties in teaching activities every day, and a supervisor who can assess teacher performance, whether there is anything that needs to be improved and whether there is anything that needs to be followed up for the teacher's teaching and learning process activities every day. Therefore, a good leadership spirit is a principal who can protect and be a good leader for teachers in improving the teacher's ability to educate their students.